Penggunaan Metode Problem Solving Terhadap Efektivitas Belajar Siswa Pada Mata Pelajaran Al-Qur'an Hadist Kelas IX di MTS Negeri 4 Karawang - Nia Nur'aeni; H. Masykur H. Mansyur; H. Abdul Kosim (Jurnal Ilmiah Wahana Pendidikan, 2021)
He success of al-qur teacher in increasing learning motivation, as well as conducting online learning is the teacher's ability to innovate in designing materials. Problem solving learning method "Problem Solving" and adjusting the material in learning. Islamic education can be interpreted as an effort to plan in preparing people to know, understand, appreciate and believe in the teachings of the Islamic religion. With the Problem Solving method that has been tested at Mts NegeriNegeri 4 Karawang and produces an analysis that learning using this method is successful so that it does not create al-qur passive but active learning atmosphere, students seem enthusiastic even though they are online, because not all students can use E-Learning but they are very enthusiastic to participate in this distance learning.